VD_FINDINFO HC / 2011 / 672 vom 28. Oktober 2011 - VD Tribunal cantonal (2011)
PROCÈS DEVENU SANS OBJET, DÉPENS, MESURE PROVISIONNELLE, RETRAITVOIE DE DROIT | 121 CPC, 160 CPC, 92 CPC, 72 PCF, 319 let. a CPC (CH), 322 al. 1 CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)